(untitled) (American & British Studies Annual, 2015)
No fiction writer wrote substantively about intra-racial snobs among African Americans before Charles W. Chesnutt. In his “Blue Vein Society” stories, this snobbery is acutely expressed through moneyed cultural edification in “The Wife of His Youth” as well as in blatantly racial terms in “A Matter of Principle.” Long an admirer of Vanity Fair, Charles W. Chesnutt shared with the early Thackeray a keen interest in satirically exposing the hypocrisy of the haughty “higher” society. In this contribution, I attempt to demonstrate the impact of Thackeray’s works on the strategies of Chesnutt’s depictions of the African American snob.